2008
DOI: 10.1016/j.bbamem.2007.12.021
|View full text |Cite
|
Sign up to set email alerts
|

VCAM-1 directed immunoliposomes selectively target tumor vasculature in vivo

Abstract: Targeting the tumor vasculature and selectively modifying endothelial functions is an attractive anti-tumor strategy. We prepared polyethyleneglycol modified immunoliposomes (IL) directed against vascular cell adhesion molecule 1 (VCAM-1), a surface receptor over-expressed on tumor vessels, and investigated the liposomal targetability in vitro and in vivo. In vitro, anti-VCAM-1 liposomes displayed specific binding to activated endothelial cells under static conditions, as well as under simulated blood flow con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
82
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(86 citation statements)
references
References 49 publications
3
82
0
1
Order By: Relevance
“…Targeting of angiogenic vessels is an attractive approach to specifically deliver reagents into tumors, especially if tumor-specific targeting molecules have not been identified. Several investigators have described in vivo tumor-homing capacities of liposomes tagged with tumor endothelium-specific peptides or Abs such as RGD and NGR peptides and VCAM-1-specific Abs (31)(32)(33). Similar to these studies, we also observed that vascular-directed lipid vesicles localize to different intratumoral compartments compared with nonspecific control liposomes (31,33).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Targeting of angiogenic vessels is an attractive approach to specifically deliver reagents into tumors, especially if tumor-specific targeting molecules have not been identified. Several investigators have described in vivo tumor-homing capacities of liposomes tagged with tumor endothelium-specific peptides or Abs such as RGD and NGR peptides and VCAM-1-specific Abs (31)(32)(33). Similar to these studies, we also observed that vascular-directed lipid vesicles localize to different intratumoral compartments compared with nonspecific control liposomes (31,33).…”
Section: Discussionsupporting
confidence: 76%
“…Several investigators have described in vivo tumor-homing capacities of liposomes tagged with tumor endothelium-specific peptides or Abs such as RGD and NGR peptides and VCAM-1-specific Abs (31)(32)(33). Similar to these studies, we also observed that vascular-directed lipid vesicles localize to different intratumoral compartments compared with nonspecific control liposomes (31,33). Lipid particles coated with cyclic RGD as targeting ligand for ␣ v ␤ 3 integrin, for instance, specifically bind to the tumor vessel wall, whereas control liposomes extravasate into tumor parenchyma (31).…”
Section: Discussionmentioning
confidence: 99%
“…The binding affinity of the ligands influences the tumor penetration owing to the "binding-site barrier." For targets in which cells are readily reachable, usually the tumor vasculature, because of the dynamic flow environment of the bloodstream, high affinity binding appears to be preferable (Adams et al, 2001;Gosk et al, 2008;Danhier et al, 2010). Various anti-cancer therapeutics, grouped under the name "ligand targeted therapeutics," are classified into different classes based on the approach of drug delivery (Allen, 2002;Danhier et al, 2010).…”
Section: Active Targetingmentioning
confidence: 99%
“…Consequently, in this strategy, ligand-targeted nanocarriers bind to and kill angiogenic blood vessels and indirectly, the tumor cells that these vessels support, mostly in the tumor core. The advantages of the tumoral endothelium targeting are; i) there is no need of extravasation of nanocarriers to achieve to their targeted site, ii) the binding to their receptors is directly possible after intravenous injection, iii) the possible risk of emerging resistance is reduced due to the genetically stability of endothelial cells as compared to tumor cells, and iv) the majority of endothelial cells markers are expressed whatever the tumor type, involving an ubiquitous approach and an ultimate broad application spectrum (Gosk et al, 2008;Danhier et al, 2010). The major targets of the tumoral endothelium include:…”
Section: Targeting Of Tumoral Endotheliummentioning
confidence: 99%
“…A variety of ligands has been used such as antibody fragments and mononuclear antibody and used for macromolecules which are peptides and proteins small molecules that include carbohydrates and folic acid. The binding similarity of ligands effects the cancer penetration due to its binding location barrier and dynamic blood flow [30,31]. The active target treatment of nano-liposomes not only could improve the targeting effect in pancreatic cancer, but also could decrease the toxic and side-effect.…”
Section: Active Targetedmentioning
confidence: 99%